Pilit sang tumandok - Alobin, Flor Kenneth; Arguelles, Eden.; Chua, Pamela; Deocariza, Roy.; Faduga, Majella; Garcia, Rachel; Libo-on, Mary Grace; Salangsang, Donna; Tejida, Janel; Vargas, Ella. (2001.)
Executive summary - "Pilit sang Tumandok" specializes in presenting, making, packaging, and selling native delicacies; not only to the Ilonggo people but also to tourists and balikbayans. The store is strategically located at the SM City Iloilo to cater to the needs and wants of the people going there. Most people find the place reasonable enough to meet their errands and experience pleasure at the same time. Having a wide variety of establishments, the people find the place more accessible than the other malls downtown. The company would like to emphasize on improving the value of our native foods and make it into a fine delicacy, will create a special kind and innovative kinds of native products. It will be presented with an attractive innovation at very reasonable prices. Also, the company would also like to enhance the scene of selling native foods into a more creative way. It is very important for the company to present the product while at the same time preserving its value and sense of being a " tumandok" product/food, even with a more modernize packaging style. This would now lead us to the 4 P's. The company would like to focus more on this subject because these are the most important part on our marketing strategies. As the group mentioned earlier, the shop will be put up at the SM City. The company choose this place because it's where people usually go for window-shopping and recreation. Whenever the place is new, the people got the connotation of how nice it is to go there. "Pilit sang Tumandok" specializes in selling native products, especially pilit, and rice-made products, rice as the staple food of the Philippines. The biggest challenge for the company is to present a wide variety of native products to the people while instilling the Ilonggo lifestyle. And lastly, to be able to stand out from the rest; from the competitors and also from the penetration of the fast food chains. The prices of the products are of much higher prices from the rest of the competitors, affected by the innovations in packaging and high quality ingredients. Needless to say, we are still offering affordable prices because our products are of high quality and have longer shelf life. The company would like to take emphasis on advertisements, even to incur much costs on it. At present, the company believes that a greater number of households watch T.V., and this would be an effective advertising medium. T.V. advertisements play a much greater role in presenting the products, because people will not only hear the characteristics of the products but at the same time have a visual presentation of the products features itself. Radio airplays and distribution of flyers will also help in presenting the product to the people. Also, the company will have a taste test to attract more customers and to really convince them of the quality and the taste of the products. "Pilit sang Tumandok" aims to preserve the Ilonggo culture by promoting its pilit and rice based native foods/delicacies made from the finest and superior quality ingredients.
Business Plan (Mgt 138 - Business Plan) -- [Iloilo City : University of the Philippines in the Visayas-College of Management], April 2001.